2022
DOI: 10.48550/arxiv.2211.03300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HFedMS: Heterogeneous Federated Learning with Memorable Data Semantics in Industrial Metaverse

Abstract: Federated Learning (FL), as a rapidly evolving privacy-preserving collaborative machine learning paradigm, is a promising approach to enable edge intelligence in the emerging Industrial Metaverse. Even though many successful use cases have proved the feasibility of FL in theory, in the industrial practice of Metaverse, the problems of non-independent and identically distributed (non-i.i.d.) data, learning forgetting caused by streaming industrial data, and scarce communication bandwidth remain key barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…• Applications. Recent studies [58,59] have shown that FL can be broadly applicable in the IoT industry, such as in smart healthcare and smart cities, etc. In addition, FL also helps detect malicious attacks in federated IoT systems.…”
Section: Iot Of Fl4mmentioning
confidence: 99%
See 1 more Smart Citation
“…• Applications. Recent studies [58,59] have shown that FL can be broadly applicable in the IoT industry, such as in smart healthcare and smart cities, etc. In addition, FL also helps detect malicious attacks in federated IoT systems.…”
Section: Iot Of Fl4mmentioning
confidence: 99%
“…There is a need to devise efficient methods for FL to address the redundancy and unrealistic nature of heterogeneous data in the metaverse. In the industrial metaverse, HFedMS [58] reduces the data heterogeneity of FL by using dynamic grouping and training mode conversion. Historical data semantics are compressed to compensate for forgotten knowledge.…”
Section: Challengementioning
confidence: 99%